PENERAPAN ANALISIS GEROMBOL DAN BIPLOT (STUDI KASUS: HASIL PERTANIAN DAERAH TERTINGGAL DI PROVINSI PAPUA BARAT) - Indah Ratih Anggriyani; Dariani Matualage; Esther Ria Matulessy (Jurnal Natural, 2018)
One of the potential of the seven districts underdeveloped areas in West Papua Province is agriculture. In order to develop agricultural potential, an overview of agricultural products is needed including the similarity of regional characteristics and the relative position of the region. The similarity of regional characteristics to agricultural product can be known by cluster analysis. The relative posistion of the area with agricultural results is known by biplot analysis. Bintuni Bay Regency, South Sorong Regency, Tambrauw Regency and Maybrat Regency have the same characteristics in producing agriculture while Teluk Wondama Regency, Sorong Regency and Raja Ampat Regency have different characteristics. The relative position of agricultural products with the regency is Sorong Regency producing the highest number of food crops while the largest producer of horticulture fruits and vegetables are Teluk Wondama Regency and Raja Ampat Regency.